PRACTICAL TRAINING ON SPSS-BASED DATA ANALYSIS TO STRENGTHEN BUSINESS RESEARCH AND STUDENT FINAL PROJECTS - Harju, Leon Mitra; Edwar, Rizka Cintya; Toii, Indra Eka Wardana; Kuddy, Aprianto La’lang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community engagement activity was designed to improve the statistical competencies of Management students at Cenderawasih University, with emphasis on the practical use of SPSS for academic research and undergraduate thesis preparation. Held on November 14, 2025, the program involved 55 seventh-semester students who engaged in interactive explanations, software demonstrations, and guided exercises. The training targeted students’ limited understanding of quantitative techniques by introducing systematic procedures such as identifying variables, entering data, conducting classical assumption tests, and applying multiple linear regression. A discussion session supported participants in mastering each analytical stage and developing independent problem-solving skills. The outcomes showed clear progress in students’ ability to execute and interpret tests for normality, multicollinearity, heteroscedasticity, autocorrelation, and linearity, along with regression results. Overall, the program significantly strengthened their statistical literacy and supported the enhancement of quantitative research quality in the Management Department.